Is Normal Pressure Hydrocephalus more than a mechanical disruption to CSF flow? - Tully, B; Byrne, J; Ventikos, Y (2010)
This work proposes a new theoretical framework for the water transport in the cerebral environment. The approach is based on Multiple-Network Poroelastic Theory (MPET) and is a natural extension of poroelasticity, a well reported technique applied to cerebrospinal fluid (CSF) transport. MPET accounts for the transport of CSF and blood simultaneously, as they permeate and deform the cerebral tissue. To demonstrate the strength of this approach, MPET is applied to one of the most paradoxical and non-intuitive cerebral pathologies, Normal Pressure Hydrocephalus (NPH). It is shown, for the first time, that clinically relevant ventricular deformations can be observed in the case of totally unobstructed, patient-specific aqueducts. Cerebral diseases are recognised as pivotal in healthcare; they relate to a whole host of unmet clinical needs. We are convinced that basic understanding of fluid transport, as provided by a validated MPET model, is the most promising way to address these needs meaningfully, in a clinical setting.